The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/cpr.12720
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0061825 (circ‐TFF1) contributes to breast cancer progression through targeting miR‐326/TFF1 signalling

Abstract: Objectives Circular RNAs (circRNAs) are RNA transcripts that belong to non‐coding RNAs (ncRNAs), whose implication in human cancers has been recently demonstrated. However, the specific role of multiple circRNAs in breast cancer remains unidentified. Materials and methods Microarray analysis and bioinformatics analysis were applied to select circRNA and miRNA, respectively. The loop structure of circ‐TFF1 was confirmed using RNase R treatment, divergent primer PCR and Sanger sequencing. qRT‐PCR and Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 32 publications
3
63
0
Order By: Relevance
“…Some circRNAs, such as circGFRA1 and circ-TFF1, can bind to cognate linear transcripts to sequester mRNA from translation and thereby trigger the decrease of protein expression [ 18 , 19 ]. Here, we found that linear NOL10 expression was significantly down-regulated in BC tumor tissues compared with that in adjacent normal tissues (Additional file 1 : Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…Some circRNAs, such as circGFRA1 and circ-TFF1, can bind to cognate linear transcripts to sequester mRNA from translation and thereby trigger the decrease of protein expression [ 18 , 19 ]. Here, we found that linear NOL10 expression was significantly down-regulated in BC tumor tissues compared with that in adjacent normal tissues (Additional file 1 : Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Wang et al showed that hsa_circ_0000467 could sponge miR‐326‐3p and promote gastric cancer development via enhancing cyclin D1 31 . In another study, miR‐326 interacted with circ‐TFF1 in breast cancer progression through regulating TFF1 expression 32 . These studies indicate that expression of miR‐326 is modulated by multiple circRNAs and miR‐326 holds different roles in different cancers.…”
Section: Resultsmentioning
confidence: 97%
“…Breast cancer has been a major public health problem worldwide among women ( 1 3 ), and thus breast cancer research has an important social significance. Recently, many related studies have shown that circ_RNF111 and circ_ABCB10 contribute to paclitaxel resistance in breast cancer ( 40 , 41 ), circ_ZEB1 acts as an oncogene in triple-negative breast cancer ( 42 ), circ_TFF1 contributes to breast cancer progression ( 43 ), circ_0000526 blocks the progression of breast cancer ( 44 ), circulating circ_RNA hsa_circ_0001785 acts as a diagnostic biomarker for breast cancer ( 45 ), etc. In the present study, the major focus was on BLBC molecular subtype, and protooncogene circ_NOTCH3 was first identified to act as a sponge for miR-205-5p, which played a crucial role in its development and progression.…”
Section: Discussionmentioning
confidence: 99%